Electrical and photocatalytic behaviour of TAOxNy magnetron sputtered thin solid films - Cristea, D. (2013)
Tantalum oxynitride thin films were deposited by reactive magnetron sputtering in a N2+O2 (85%+15%) atmosphere, with increasing total reactive gas flows. The chemical composition was determined by RBS and the structural development by XRD. The electrical resistivity was measured using the 2-point and 4-point probe techniques. The photocatalytic behavior was determined on glass samples in UV, using methylene-blue as a pollutant. It was observed that, depending on the deposition process parameters, the samples can be divided into 4 zones, each with a characteristic structure and subsequent behavior. The samples from zone I can be attributed to the β-Ta phase, metallic, conductive. The samples from zone II can be attributed to a fcc Ta(O, N) structure, with N/Ta higher than O/Ta, with increasing electrical resistivity. The samples from zone III are oxide-like, amorphous, electrically insulating.